2010
DOI: 10.1093/bja/aeq143
|View full text |Cite
|
Sign up to set email alerts
|

Precision and accuracy of a new device (CNAP™) for continuous non-invasive arterial pressure monitoring: assessment during general anaesthesia

Abstract: CNAP provides real-time estimates of arterial pressure comparable with those generated by an invasive intra-arterial catheter system during general anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
119
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 157 publications
(123 citation statements)
references
References 23 publications
(17 reference statements)
2
119
2
Order By: Relevance
“…This has important implications, as CNAP is more likely than NIBP to leave the anaesthetist without blood pressure readings for a significant period (> 2 min). One reason for the increased recalibration rate in CNAP was that this study involved awake patients with voluntary upper limb movement, whereas the previous accuracy study was conducted under general anaesthesia [7]. The invasive arterial blood pressure vs CNAP defined a fast change in arterial pressure as a change of blood pressure of 20 mmHg, within a 3-min period, and concluded that both devices found a similar incidence of this change [7].…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…This has important implications, as CNAP is more likely than NIBP to leave the anaesthetist without blood pressure readings for a significant period (> 2 min). One reason for the increased recalibration rate in CNAP was that this study involved awake patients with voluntary upper limb movement, whereas the previous accuracy study was conducted under general anaesthesia [7]. The invasive arterial blood pressure vs CNAP defined a fast change in arterial pressure as a change of blood pressure of 20 mmHg, within a 3-min period, and concluded that both devices found a similar incidence of this change [7].…”
Section: Discussionmentioning
confidence: 98%
“…One reason for the increased recalibration rate in CNAP was that this study involved awake patients with voluntary upper limb movement, whereas the previous accuracy study was conducted under general anaesthesia [7]. The invasive arterial blood pressure vs CNAP defined a fast change in arterial pressure as a change of blood pressure of 20 mmHg, within a 3-min period, and concluded that both devices found a similar incidence of this change [7]. However, during caesarean section, the blood pressure may change by considerably more than 20 mmHg from the baseline within a time period of < 3 min.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations